2010
DOI: 10.1667/rr2147.1
|View full text |Cite
|
Sign up to set email alerts
|

Pifithrin-α as a Potential Cytoprotective Agent in Radiotherapy: Protection of Normal Tissue without Decreasing Therapeutic Efficacy in Glioma Cells

Abstract: Activation of p53 has been causally linked to normal tissue damage after irradiation. Pifithrin-α (PFT-α), a specific inhibitor of p53, has been suggested as a combinatory agent in the treatment of p53-deficient tumors in which inhibition of p53 would not compromise therapeutic efficacy but would decrease p53-mediated side effects in normal tissue. We tested this concept for radiotherapy of p53-deficient and -proficient glioma. We observed significant interaction of PFT-α with radiation-induced G(1) checkpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To prevent and inhibit radiation-induced toxicity, the early prevention of epithelial, endothelial, and stem cell deaths is one of the primary options that can be proposed. These interventions imply the administration of drugs delivered prophylactically (Table 1) including inhibitors of pro-apoptotic molecules, such as the transient blockade of p53 (Pifithrin); 10,11 the inhibition of p-53 upregulated modulator of apoptosis (Puma Inhibitors) or the inhibition of the ceramide pathway in endothelial cells. 16,17 Alternatively, stimulation of antiapoptotic molecules such as NF-ҡB by the flagellin-derivative, CBLB502 18,19 protects microvascular endothelial cells from radiation-induced death.…”
Section: Inhibiting Radiation-induced Acute Cell Death and Depletionmentioning
confidence: 99%
“…To prevent and inhibit radiation-induced toxicity, the early prevention of epithelial, endothelial, and stem cell deaths is one of the primary options that can be proposed. These interventions imply the administration of drugs delivered prophylactically (Table 1) including inhibitors of pro-apoptotic molecules, such as the transient blockade of p53 (Pifithrin); 10,11 the inhibition of p-53 upregulated modulator of apoptosis (Puma Inhibitors) or the inhibition of the ceramide pathway in endothelial cells. 16,17 Alternatively, stimulation of antiapoptotic molecules such as NF-ҡB by the flagellin-derivative, CBLB502 18,19 protects microvascular endothelial cells from radiation-induced death.…”
Section: Inhibiting Radiation-induced Acute Cell Death and Depletionmentioning
confidence: 99%
“…Activation of p53 has been linked to normal tissue damage after irradiation, as p53 eliminates the damaged cell by apoptosis 42 . Inhibitors of p53 like pifithrin-alpha, particularly in cells that were inadvertently exposed to radiation have the potential to salvage the tissue 43 (Fig. 3).…”
Section: Modifiers Of Cell Signallingmentioning
confidence: 99%
“…In glioma cells, it was shown that there was an increase in survival of normal astrocytes and fibroblasts post-irradiation. It is also important to note that there were no changes in radiosensitivity of the tumor to irradiation using pifithrinalpha 43 . Therefore, this agent may prove valuable in protecting normal tissues from the side effects of radiotherapy while maintaining treatment efficacy.…”
Section: Modifiers Of Cell Signallingmentioning
confidence: 99%